1986
DOI: 10.1016/0014-5793(86)81025-0
|View full text |Cite
|
Sign up to set email alerts
|

ATP can promote activation and deactivation of the rod cGMP‐phosphodiesterase

Abstract: The AT (amplified transient) signal is a flash-induced increase of the near-infrared light scattering from isolated bovine rod outer segments and is interpreted as a monitor of cGMP-phosphodiesterase activation [(1985) FEBS Lett. 188, 15-201. We have investigated the effects of ATP and cyclic GMP on this signal. It has been found that ATP enhances the AT signal, the relative effect being the largest for low photoexcitation (-1 rhodopsin per disc membrane). At a high rhodopsin turnover, which saturates the AT a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

1987
1987
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 18 publications
1
7
0
Order By: Relevance
“…Retinas were incubated for 10 minutes in hypotonic buffer supplemented with 1 mM ATP [Bitensky et al, 1975;Kamps and Hofmann, 1986] and 5μM GTPγS [Wensel and Stryer, 1986]; then, for 2 extra minutes, they were either maintained in the dark or exposed to room light. Retinas were then homogenized, centrifuged for 10 minutes at 8,000 g and supernatants collected.…”
Section: Pde Activity Assaymentioning
confidence: 99%
“…Retinas were incubated for 10 minutes in hypotonic buffer supplemented with 1 mM ATP [Bitensky et al, 1975;Kamps and Hofmann, 1986] and 5μM GTPγS [Wensel and Stryer, 1986]; then, for 2 extra minutes, they were either maintained in the dark or exposed to room light. Retinas were then homogenized, centrifuged for 10 minutes at 8,000 g and supernatants collected.…”
Section: Pde Activity Assaymentioning
confidence: 99%
“…Among the several types of LS signal described previously is the amplified, transient ("AT") response recorded from permeabilized bovine ROS (8,9). The AT signal appears to monitor the activation of PDEi.e., G* + PDE-I G*'I + PDE*, where I is the inhibitory subunit of PDE (1,10).…”
mentioning
confidence: 99%
“…In addition to R*-transducin interactions, transducinphosphodiesterase (PDE) interactions were shown to generate a distinct scattering signal. This amplified, transient (AT) signal was demonstrated in suspensions of bovine rod OSs (62,63) and bovine retinal explants (64). Pepperberg et al showed that the scattering changes were present in low Na + solutions, even when the ERG response was completely extinguished (64), thereby ruling out the possibility that the former were due to the shifting Na + gradient underlying membrane hyperpolarization.…”
Section: Optical Signatures Of Signal Transduction In Neurons or Intrinsic Signalsmentioning
confidence: 98%